Identifikasi Jenis Bahan Aktif dan Penggunaan Insektisida Antinyamuk serta Kerentanan Vektor DBD terhadap Organofosfat pada Tiga Kota Endemis DBD di Provinsi Banten - Joni Hendri; Asep Jajang Kusnandar; Endang Puji Astuti (ASPIRATOR - Journal of Vector-borne Disease Studies, 2016)
The increasing cases of Dengue Hemorrhagic Fever (DHF) in various places leads to increased efforts to control the Aedes aegypti mosquito populations using anti-mosquito insecticide. The use of insecticides continuously, the absence of insecticide rotation and errors in the application has been lead to insecticide resistance of dengue vector. The purpose of this study is (1) to identify active ingredients of insecticide; (2) used of anti-mosquito insecticide that has been used by households and programs, (3) as well as knowing the susceptibility status of Aedes aegypti to organophosphate insecticides (Malathion 0,8% and Temephos 0.02 ppm). Descriptive research with cross sectional approach conducted in three highest endemic cities in Banten province: Cilegon City, Serang City, and South Tangerang City. Identification of anti-mosquito insecticide has been done by interview, and identifying health centers and Health Service reports. The results showed that most respondents have been using anti-mosquito insecticide applied daily at night. Respondents prefer to use repellent which can be applied by swab. Based on the active ingredient, D-alethrin is a type of active ingredients which mentioned most often, followed by Pralethrin and Diethyltoluamide (DEET). Insecticides used by the program are Malathion and Pirimiphos-methyl, rotated by Cypermethrin. Susceptibility test results showed that Aedes aegypti is not susceptible to Malathion 0,8 % and Temephos 0.02 ppm.